Political satire and dissent towards constituted power in George Orwell's “Animal Farm” - Roa, Guillermo (Frónesis, 2025)
The purpose of this research is to analyze the political satire and dissent to power constituted based on the work rebellion Farm author George Orwell, as an expression of the ambiguity of political discourse for the production, control and perpetuation of power. In general, it was concluded that the role of satire in political history has been and always will be the transformation of the policies implemented by those in power, and you could say that through it a form of peaceful protest, which is north get away the unreal veil and observe the reality that any society could be raising with which political change can be found within the state as socio- political organization.